The Commission of National Education: Research Prospects within Intellectual Culture - Janeczek, Stanisław (Roczniki Kulturoznawcze, 2010)
This paper discusses the trends in researches indispensable for an integral approach to the Commission of National Education, an essential cultural and social phenomenon. As it is universally agreed, the Commission was the first European ministry of education. It is necessary to go beyond the circle of studies typical of school structure in its history, i.e. such that concentrates on the presentation how a school structure functions in its formative and didactic aspects, especially the network of schools, population of teachers and pupils, and also didactic aids that were used. Education should be analysed also within the overall cultural formation, a concrete school system, especially that its social role in the Enlightenment went considerably beyond the scope of contemporary education. Accordingly, we are obliged to show, among other things, the European context of the Enlightenment school reforms, commonly linked with the French reforms, and the school standards that preceded the reforms. One should also make a more thorough analysis of textbooks used in this system of education, taking into consideration the then level of learned and philosophical culture, or even traces that the intellectual tendencies that affected formation and education proper of this learned institution.